Included in top researchers list (ScholarGPS, field: Arts and Humanities) - Tsapatsoulis, Nicolas (My University, 2026)
https://scholargps.com/scholars/86463292008265/nicolas-tsapatsoulis
Keywords: World's Top Scientists